Gambaran Pengetahuan dan Pola Swamedikasi pada Mahasiswa Kesehatan di Dua Perguruan Tinggi di Kota Medan: Description of Knowledge and Self-Medication Pattern in Health Students at Two Higher Educations in Medan City - Faiza Adinda; Wahyudi Wahyudi; Mawaddah Sri Rezeki Dalimunthe; Amalia Rahmi Nasution; Nurly Fadhila; Shelly Febrina (JURNAL FARMASI DAN MAKANAN, 2023)
Self-medication is a healing practice carried out independently by diagnosing symptoms, determining drugs and using drugs that are consumed without a doctor's prescription. The purpose of this study was to describe the knowledge and patterns of self-medication of health students at two tertiary institutions in the city of Medan. The research method is descriptive quantitative with a survey design. The data collection is the distribution of questionnaires viagoogle forms.Processing data using techniquesprobability samplingthat issimple random sampling.The results of the research are that self-medication knowledge in the good category is owned by PT(A) 57.7% and 63.5% PT(B), very good 38.5% PT(A) and 30.8% PT(B), not good 3.8% PT(A) and 3.8% PT(B), and not good at PT(B) at 1.9%. In terms of selfmedication patterns/efforts, 71.2% PT(A) and 51.9% PT(B) were in good category, very good 26.9% PT(A) and 44.2% PT(B). not good 1.9% PT(A) and 1.9% PT(B), and not good 2% on PT(B). The conclusion of this study shows that health students from both PTs have knowledge in the good category, but PT(A) is slightly better regarding knowledge (96.2%) and self-medication patterns (98.1%) than knowledge (96.3%) and self-medication pattern (96.1%) PT(B).